Rapid diagnosis of trisomy 13 of maternal origin by quantitative fluorescent polymerase chain reaction analysis in a pregnancy with fetal holoprosencephaly, premaxillary agenesis, postaxial polydactyly of left hand and overriding aorta - Chih-Ping Chen; Chao-Yun Wu; Schu-Rern Chern; Shin-Wen Chen; Fang-Tzu Wu; Mang-Shang Lee; Wayseen Wang (Elsevier, 2021)
Objective: We present rapid diagnosis of trisomy 13 of maternal origin by quantitative fluorescent polymerase chain reaction (QF-PCR) in a pregnancy with multiple fetal abnormalities. Case report: A 35-year-old, primigravid woman was referred for amniocentesis at 24 weeks of gestation because of multiple congenital anomalies in the fetus. Prenatal ultrasound at 23 weeks of gestation revealed holoprosencephaly, premaxillary agenesis, postaxial polydactyly of the left hand and overriding aorta. Amniocentesis was performed subsequently, and QF-PCR analysis using the polymorphic DNA markers of D13S789 (13q22.3), D13S790 (13q31.1) and D13S767 (13q31.3) on the DNA extracted from uncultured amniocytes and parental bloods showed trisomy 13 of maternal origin. Conventional cytogenetic analysis on the cultured amniocytes confirmed trisomy 13. The pregnancy was subsequently terminated, and a malformed fetus was delivered with multiple anomalies consistent with the prenatal diagnosis. Conclusion: QF-PCR analysis is useful for rapid confirmation of trisomy 13 and the parental origin when prenatal ultrasound findings are suspicious of fetal trisomy 13.